Hand and foot edema: is it a feature of adult Kawasaki disease? Case report and comparison between child and adult disease. - Shelleh, H.H. (European Journal of Pediatric Dermatology, 2007)
Kawasaki disease (KD) is primarily a disease of childhood, being rarely encountered in adults. It has precious diagnostic criteria in which each criterion is almost unique. Edema, erythema or desquamation of the hands and feet form three substitutes in one criterion. We report a case of adult KD in which hand and foot edema did not occur. On reviewing the reported cases of adult KD in literature we found that hand and foot edema was not reported as well. We think that, due to differences in electrolytes distribution between adults and children and differences in ratios of intracellular and extracellular fluids as well, hand and foot edema may not develop in adults as part of the inflammatory process of KD, and it should not be awaited for diagnosis. For this reason, the diagnostic criteria of KD, which were primarily set up for children, should undergo some changes in adults in order to overpass this potential gap, otherwise the diagnosis making will become more critical in adulthood.